DESDE LAS ÉTICAS HACIA LA POLÍTICA DE LA LIBERACIÓN DE ENRIQUE DUSSEL. APROXIMACIÓN CRÍTICA Y DEBATES SOBRE SU FILOSOFÍA DE LA LIBERACIÓN. - Díaz Fernández, José (Revista de Filosofía (00348236), 2022)
The article presents a critical reading of Enrique Dussel's philosophy, where the breaks and continuities of his early and mature ethical project are considered. The objective of the research is to explore and expose the author's thinking in relation to the problems, criticisms and controversies that it presents. For this, the early ethical and political positions of his philosophy are clarified, the place of criticism of Horacio Cerutti, the structure of mature ethics, the debate with Karl-Otto Apel, the structure of the Politics of Liberation and the criticism of Santiago Castro-Gómez. The article presents a secular and critical reading of one of the most relevant liberation philosophies in Latin America.